Optimization of anthracene biodegradation by indigenous Trichoderma lixii and Talaromyces pinophilus using response surface methodology - Samson O. Egbewale; Ajit Kumar; Mduduzi P. Mokoena; Ademola O. Olaniran (Ecotoxicology and Environmental Safety)
Two indigenous fungal strains, Trichoderma lixii FLU1 (TlFLU1) and Talaromyces pinophilus FLU12 (TpFLU12) showed potential to biodegrade anthracene. Response Surface Methodology (RSM) employing Box-Behnken Design (BBD) and Central Composite Design (CCD) methods optimized crucial physicochemical parameters like pH, temperature, biomass, substrate concentration and media composition. BBD maximized anthracene biodegradation efficiency by predicting 98.7–103.2 %. Analysis of Variance confirmed the model's accuracy with a significant F-value of 51.0 at p<0.0001 while the quadratic regression model showed a high R² value 0.9808. CCD predicted 100 % degradation efficiency which were validated for TlFLU1 and TpFLU12 respectively on day 8 and 12 at pH 4 and 5, temperatures 30°C and 25°C, with 20 mm biomass size and 200 mg/L anthracene. 9,10-anthraquinone and phthalic acid were detected as metabolites formed during the anthracene degradation by TlFLU1 and TpFLU12 after validation of the optimization process. Acute toxicity tests showed that the degradation media toxicity reduced as evidenced by increased in survival rate (log CFU/mL) of Vibrio parahaemolyticus after 6 h exposure. Despite reduced toxicity, both strains were classified as harmful based on effective concentration (EC50) and toxicity unit (TU) (20.92±1.32 mg/L and 4.78 % for TlFLU1 and 35.29±1.55 mg/L and 2.83 % for TpFLU12). This systematic optimization approach supported by robust statistical analyses and a deep exploration of biodegradation mechanisms holds the promise of more efficient and sustainable methods for remediating PAH-contaminated environments.